2005
DOI: 10.2193/0022-541x(2005)069[0689:bbrtva]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Bird Response to Varying Amounts of Basal Area Retention in Riparian Buffers

Abstract: We examined response of breeding bird communities to forest harvest that removed varying amounts of tree basal area from riparian buffers on a 2to 4-m-wide stream in northern Minnesota, USA. We compared bird species and communities in 30-m-wide riparian buffers along the stream. Buffers were established within plots in which upland forests were clear-cut (basal area 2 m 2 /ha) according to standard local forest management practice. Buffers had 4 treatments (3 plots/treatment): (1) no harvest (riparian control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
3
8
1
Order By: Relevance
“…This observation is also consistent with other studies (Hanowski et al, 2005;Holmes and Pitt, 2007) that found similar responses of the mature forest avian species to timber harvesting. The Ovenbird, a species that we observed to have a significant decline following harvest in all treatment plots, is a "species of greatest conservation need" in the Minnesota Department of Natural Resources' Comprehensive Wildlife Conservation Plan (Minnesota Department of Natural Resources, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation is also consistent with other studies (Hanowski et al, 2005;Holmes and Pitt, 2007) that found similar responses of the mature forest avian species to timber harvesting. The Ovenbird, a species that we observed to have a significant decline following harvest in all treatment plots, is a "species of greatest conservation need" in the Minnesota Department of Natural Resources' Comprehensive Wildlife Conservation Plan (Minnesota Department of Natural Resources, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Hanowski et al (2005) is one of the few replicated experimental studies that examined varying levels of residual basal area. They found that more edge and early successional species and individuals colonized harvested RMZs after harvest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to the results of many other studies in which total avian abundance in buffer strips actually increased post-harvest [10,15,17,[45][46][47]. Post-harvest increases in abundance in buffer strips have been attributed to "crowding in" of individuals of mature forest species displaced from nearby clear cuts [10,17,45].…”
Section: Breeding Bird Response To Partial Harvestingcontrasting
confidence: 90%
“…These differences existed, even though residual basal areas were similar across all 3 blocks. Hanowski et al [47] have suggested that the amount of basal area left remaining in riparian buffers adjacent to clear cut areas will differentially impact breeding bird communities. We agree, but our study also shows that, at least at lower harvesting intensities, the amount of basal area removed may be just as important.…”
Section: Breeding Bird Response To Partial Harvestingmentioning
confidence: 99%